2017 IEEE 36th Symposium on Reliable Distributed Systems (SRDS) 2017
DOI: 10.1109/srds.2017.25
|View full text |Cite
|
Sign up to set email alerts
|

PULP: Achieving Privacy and Utility Trade-Off in User Mobility Data

Abstract: Leveraging location information in location-based services leads to improving service utility through geocontextualization. However, this raises privacy concerns as new knowledge can be inferred from location records, such as user's home and work places, or personal habits. Although Location Privacy Protection Mechanisms (LPPMs) provide a means to tackle this problem, they often require manual configuration posing significant challenges to service providers and users. Moreover, their impact on data privacy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Moreover, the convergence is not ensured and consequently there is no guarantee that the objectives are actually met. PULP is first presented in [7]. In this paper, we extend this previous work by developing three more configuration laws enabling a dataset owner to specify several combinations of privacy and utility objectives, and we present extensive experimental evaluations for both the modeling and the configuration parts of PULP.…”
Section: B Lppm Configurationmentioning
confidence: 94%
“…Moreover, the convergence is not ensured and consequently there is no guarantee that the objectives are actually met. PULP is first presented in [7]. In this paper, we extend this previous work by developing three more configuration laws enabling a dataset owner to specify several combinations of privacy and utility objectives, and we present extensive experimental evaluations for both the modeling and the configuration parts of PULP.…”
Section: B Lppm Configurationmentioning
confidence: 94%
“…Location privacy protection mechanisms (LPPMs) are particularly interesting to limit user privacy leaks [5]. A large body of the related work has been devoted towards the latest stages of mobile crowdsourcing campaigns by improving the privacy properties of datasets once uploaded to remote servers [23,28,35].…”
Section: Fig 1 Anatomy Of a Mobile Crowdsourcing Campaignmentioning
confidence: 99%
“…We observed that these two properties are related in practice, as the application of LPPMs tends to decrease the utility of the crowdsourced dataset. This observation calls for the identification of a privacy and utility trade-off in the context of mobile crowdsourcing systems, as acknowledged by [5].…”
Section: Threats To Validitymentioning
confidence: 99%
“…For instance, ALP (Adaptive Location Privacy) [25] a framework which enables an automatic configuration of the LPPM parameters using simulated annealing. Also, PULP [9] is another system which automatically configures LPPMs according to users' objectives in term of privacy and utility. MooD is complementary to those configuration frameworks.…”
Section: Related Workmentioning
confidence: 99%